The Effect of Body Weight on Eating Behavior and Risk for Diabetes, Health Literacy Among Turkish Adults - Kadioglu, Bircan Ulas; Soylar, Pinar (Mattioli 1885, 2021)
Aim: This study was aimed to investigate the effect of body weight on eating behavior, risk for diabetes and health literacy of individuals in a primary healthcare center. Design: Body weight, eating behavior, risk for diabetes and health literacy level were evaluated in this cross-sectional descriptive study. A total of 210 individuals with normal weight (Body Mass Index (BMI) of 18.5 to <25), overweight (BMI of 25 to <30 kg/m(2)) and obese (BMI >= 30 kg/m(2)) were included in the study. The three-factor eating questionnaire (TFEQ) was used to investigate the eating behaviors of the participants. Turkish Health Literacy Scale-32 (THLS-32) and FINDRISC Type 2 Diabetes Risk Assessment Form was used. Results: A significant relationship was determined the total score of TFEQ scale and body mass index categories. The risk of diabetes was higher in obese individuals. The scores obtained from THLS-32 were lower in obese individuals. The chances of obese individuals being in the high-risk group for diabetes are 8.47 times higher compared to individuals with normal weight. According to the results of multivariate analysis, this risk is 9.92 times. Conclusions: It was determined that increased the body weight associated TFEQ scale and the risk for diabetes and also Health Literacy. Weight management practices should be conducted by a multidisciplinary team for individuals in risk group with high BMI in healthcare centers.
Keywords: Eating behavior; body weight; body mass index; diabetes mellitus; health literacy